Noise exposure impact zone hue modeling using LISA FEA V.8 - EFENDI, ST., MT, Ir.ACO WAHYUDI (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
This study aims to obtain data on the impact of noise pollution by conducting a noise test from the operation of the PLTD and modeling it to get the noise impact hue. Finite element software modeling the impact of noise generated from the operation of PLTD to determine the hue of the noise impact. LISA, a popular finite element analysis application, was used to estimate and complete this study using the finite element model. Noise data retrieval, some data is carried out according to the engine power load during production and the machine stops with a certain distance reference to the affected area, namely residential areas, with a zone radius of up to 100 m from the machine point. The condition of the impact of noise exposure that occurs, where in general the area that has a major impact on settlements is a linear area of openings at the noise source because noise waste is free to come out of building openings without any obstacles. , so that the nominal sound impact that occurs without these obstacles, the average noise value is above the 70 dB.A threshold with the category of very disturbing.